Pathological Gait Signatures of Post-stroke Dementia With Toe-Off and Heel-to-Ground Angles Discriminate From Alzheimer’s Disease - Ni, Linhui; Lv, Wen; Sun, Di; Sun, Yi; Sun, Yu; Xu, Xinxin; Chang, Mengyue; Han, Xing; Tao, Shuai; Hu, Xingyue; Cai, Huaying (Frontiers in Aging Neuroscience, 2021)
Given the low accuracy of neuropsychological tests, there is a need for a simple, reliable means, such as gait, to identify mild dementia and its subtypes. However, post-stroke dementia (PSD) and Alzheimer’s disease (AD) patients’ gait characteristics are unclear. We sought to describe their gait signatures and to explore gait parameters distinguishing PSD from cognitively normal post-stroke (PSCN) and AD patients. We divided 3-months post-stroke patients into PSCN and PSD groups based on the Mini-Mental State Examination (MMSE) scores. Thirty-one AD patients and thirty-two healthy controls (HCs) were also recruited. Ten gait parameters in one single- and two dual-task gait tests (counting-backward or naming-animals while walking) were compared among the groups, with adjustment for baseline demographic covariates and the MMSE score. Area under the receiver operating characteristic curve (AUC) was used to identify parameters discriminating PSD from PSCN and AD individuals. PSD and AD patients showed impaired stride length, velocity, stride time, and cadence, while PSD patients had altered stance and swing phase proportions (all P < 0.01, post-hoc). AD patients had smaller toe-off (ToA) and heel-to-ground angles (HtA) (P < 0.01) than HCs in dual-task gait tests. PSD individuals had a shorter stride length, slower velocity, and altered stance and swing phase percentages in all tests (P < 0.01), but a higher coefficient of variation of stride length (CoVSL) and time (CoVST), only in the naming-animals-task gait test (P < 0.001), than PSCN individuals. ToA and HtA in the naming-animals-task gait test were smaller in AD than in PSCN individuals (P < 0.01). Statistical significance persisted after adjusting for demographic covariates, but not for MMSE. Pace and the percentage of stance or swing phase in all tests (moderate accuracy), CoVST in the dual-task paradigm, and CoVSL only in the naming-animals-task gait test (AUC > 0.700, P < 0.01) could distinguish PSD from PSCN. Furthermore, the ToA and HtA in the naming-animals-task gait paradigm discriminated AD from PSD (AUC > 0.700, P < 0.01). Thus, specific gait characteristics could allow early prediction of PSD and may allow non-invasive discrimination between PSD and AD, or even other subtypes of non-AD dementia.